Does "free" higher education in South Africa make economic sense? Views of commerce students - De Jager, E.; Baard, R. (South African Journal of Higher Education, 2020)
Abstract Student protests demanding ‘free’ higher education at South Africa universities in 2015 is a reminder that there are still a lot of unresolved issues regarding the inequalities due to the apartheid era in the higher education system. Some of these issues include insufficient state funding of higher education, the increase of tuition fee and unpaid student debt. Even though ‘free’ higher education sounds appealing, the question is whether implementing ‘free’ higher education would make economic sense in South Africa. The study aimed to investigate the perceptions of commerce students at one South African university regarding the economic feasibility of ‘free’ higher education and how it might affect the South African economy. The research aimed to give a descriptive analysis of the perceptions of commerce students and were empirically investigated by means of a questionnaire, containing both open and closed questions. Gaining understanding into student perceptions can be invaluable, as they are considered the livelihood of higher education institutions. The results show that the respondents do not think that ‘free’ higher education make economic sense in South Africa as the economy is too weak and there is too much corruption and wasteful spending in government. The respondents also indicated that the economy will mostly be negatively affected by ‘free’ higher education in that there will be an increase of the financial burden on the South African economy and tax payer. They also regard other government services to be of greater importance than implementing ‘free’ higher education. The results of this study are not necessarily generalisable beyond the scope of the particular institution, but the findings do create a platform for the continued debate on the importance, economic feasibility and implementation of ‘free’ higher education in South Africa.